ANALYSIS OF JAPANESE TOURIST DEMAND TO BALI USING CO-INTEGRATION TEST AND VECTOR ERROR CORRECTION MODEL - Ni Luh Putu Suciptawati; M Sianipar (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
This study was aimed to figure out of the long term and short term correlation between -tourism price and tourist income to the tourism demand of Japanese to Bali. Quarterly data from 2003-2016 were analyzed by cointegration test and Vector Error Correction Model (VECM). The result showed that there were both long term and short term balance among research variables. At long term, the tourist income has a positive influence on tourism demand and on the other hand the tourism price has a negative one. Meanwhile at the short term the tourist income has a negative influence on the tourism demand.